The Oxford dictionary of synonyms and antonyms. (Oxford : Oxford University Press, 2014)
"Authoritative, accessible, and completely up to date, The Oxford Dictionary of Synonyms and Antonyms is an invaluable guide for anyone wanting to build their vocabulary and improve their writing skills. Over 140,000 alternative and opposite words are given with the closest, most frequently used synonyms listed first; in addition, thousands of real-life examples of usage from the Oxford English Corpus enable the reader to pinpoint the relevant word quickly and easily. Also included is a useful center section designed to improve your knowledge of the language, consisting of: a commonly confused words supplement that explains the crucial differences between similar words that are often mixed up; and a Wordfinder section that offers a selection of thematic lists - from chemical elements and clothing to phobias and flowers."--
Introduction -- Guide to the dictionary -- Labels -- Abbreviations -- The Oxford dictionary of synonyms and antonyms -- Commonly confused words -- Wordfinder.
First Edition: 1999.
Keywords: English language -- Synonyms and antonyms -- Dictionaries